Simultaneous correlation architecture for multilevel complementary sequences - Hadad, Matías Nicolás (2014)
Complementary sequences are being widely used in applications ranging from communication to radar and sonar systems. The properties of these sequences render them suitable for applications requiring signal detection in noisy environments and/or multi-user systems. The use of complementary sequences in practical applications with reduced hardware resources has promoted the development of efficient architectures that reduce the computational requirements for the generation and correlation of the sequences. An optimised architecture for the simultaneous correlation of pairs of multilevel complementary sequences is presented, which achieves that reduction by removing redundant operations. The proposal has an impact also on the correlation of binary complementary pairs of sequences of lengths of a power of 10 and 26 that use the multilevel architecture to generate the kernels.